Immunohistochemical expression and correlation of mammaglobin with the grading system of breast carcinoma - Rehman Fakeha; Nagi A; Hussain Mahwish (Wolters Kluwer Medknow Publications, 2010)
Objectives: In this study it was intended to study mammaglobin expression as a marker for the detection of breast cancer and correlate it with the Bloom-Richardson grading system of breast carcinoma. Materials and Methods: The study was conducted from May 2007 to May 2008. Tissue samples were collected from 50 patients of breast cancer in the various stages of their disease and correlated histologically with the Bloom-Richardson grading system for breast carcinoma. The clinical data of the patients were obtained from their respective files. Results: Positive immunostaining for mammaglobin was seen in 84% of breast carcinoma cases. This immunoreactivity did not correlate with histological and nuclear grades of the tumors, yet it varied according to the histological type of the tumor with ductal carcinoma showing stronger and diffuse staining than other varieties. Conclusion: These results elicit that mammaglobin is overexpressed in carcinoma breast as compared to the normal breast epithelium. This mammaglobin expression can act as a useful tool in the diagnosis of women with breast cancer.